Novel mutation in the KITLG gene in familial progressive hyperpigmentation with or without hypopigmentation. Issue 6 (18th March 2020) - Kato, Maki; Yagami, Akiko; Tsukamoto, Tetsuya; Shinkai, Yasuko; Kato, Takema; Kurahashi, Hiroki
Abstract: We herein report a novel mutation in familial progressive hyper‐ and hypopigmentation (FPHH). The KITLG gene encoding the KIT ligand protein is a disease‐causing gene for FPHH. Various disease‐causing gain‐of‐function mutations, which reside within or adjacent to the conserved VTNN motif of this gene, have been described to date. We have now identified a novel KITLG mutation, c.337G>A (p.Glu113Lys), in FPHH which is located within another ligand‐receptor interaction site.